2016
DOI: 10.1089/ars.2016.6665
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant Mechanisms in Renal Injury and Disease

Abstract: Significance: A common link between all forms of acute and chronic kidney injuries, regardless of species, is enhanced generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) during injury/ disease progression. While low levels of ROS and RNS are required for prosurvival signaling, cell proliferation and growth, and vasoreactivity regulation, an imbalance of ROS and RNS generation and elimination leads to inflammation, cell death, tissue damage, and disease/injury progression. Recent Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
513
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(556 citation statements)
references
References 342 publications
(319 reference statements)
8
513
1
11
Order By: Relevance
“…Low-level ROS function as signaling molecules for cellular proliferation and vascular homeostasis under healthy conditions [14]; however, ROS accumulate massively in the kidneys due to pathological conditions caused by angiotensin II signaling [23,24], a high-salt diet [25], hypertension [23,26], inflammation [27], hyperglycemia [28] or nephrotoxic drugs [29]. …”
Section: Oxidative Stress and Kidney Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-level ROS function as signaling molecules for cellular proliferation and vascular homeostasis under healthy conditions [14]; however, ROS accumulate massively in the kidneys due to pathological conditions caused by angiotensin II signaling [23,24], a high-salt diet [25], hypertension [23,26], inflammation [27], hyperglycemia [28] or nephrotoxic drugs [29]. …”
Section: Oxidative Stress and Kidney Diseasesmentioning
confidence: 99%
“…Kidney diseases are also thought to be related to oxidative stress [2,13,14], and basic research has generated evidence that NRF2 activation prevents kidney disease progression by protecting cells from oxidative damage. Therefore, there is a need for NRF2-activating medicines to protect against kidney diseases, for which there are currently no effective medications.…”
Section: Introductionmentioning
confidence: 99%
“…45) Moreover, it has been reported that all forms of acute and chronic renal injuries, regardless of species, is associated with enhanced generation of ROS, 46) which linked ROS to renal damage. Besides, cell senescence also plays a pivotal role in renal damage.…”
Section: Hfd and Hg Culture Comparisonmentioning
confidence: 99%
“…Oxidative stress is characterized by increased ROS and/or RNS which were indicated in both human and animal models with kidney injury (Ratliff et al, 2016). In the kidney, nitric oxide (NO) plays a great role in the regulation of physiological glomerular functions (Prabhakar, 2001).…”
Section: Discussionmentioning
confidence: 99%